PBM E-Questionnaire: Application Development and UI / UX Analysis - Fajril Pratama Kadri; Evaliata Br Sembiring (Journal of Applied Informatics and Computing, 2020)
Batam State Polytechnic declares itself as a tertiary institution which is very concerned about the quality of its education. This achievement was reported through the implementation of an education quality assurance system through study programs accredited by BAN-PT. One of the quality assurance services for education is through feedback studies on learning services through study programs. Almost every year in Batam State Polytechnic, study programs apply for accreditation to BAN-PT. Then along with these activities needed data quickly and completely. However, in reality, it is not uncommon for the drafting team to experience obstacles in obtaining the data. Based on this, in this study, an electronic PBM questionnaire application was made from several parties including lecturers, students, alumni, and alumni users (stakeholders). Making an application using the Research and Development (RnD) method and analysis in the Interface and Experience section. The results of the study with the average achievement percentage reached 88.3% showed that the user interface of the E-Questionnaire website application was very well received by the user.